Small flakes for sharp needs: Technological behaviour in the Lower Palaeolithic site of Marathousa 1, Greece - Dalila De Caro; Moritz Kuhn; Nicholas Thompson; Eleni Panagopoulou; Katerina Harvati; Vangelis Tourloukis (PLoS ONE, 2025)
Marathousa 1 (~430 ka BP), located in the Megalopolis Basin, Greece, represents the earliest documented butchery site in the Southern Balkans, providing clear evidence of a direct association between artefacts and remains of Palaeoloxodon antiquus. The lithic assemblage features a distinctive small tools industry, primarily produced from local radiolarite, comprising both simple flakes and retouched tools. Through technological analysis, raw material characterisation, experimental knapping, and statistical analyses, this study explores how Middle Pleistocene hominins organised their technological behaviour as reflected in the lithic assemblage, and how these behaviours were shaped by the resource-rich setting of the Megalopolis Basin, characterised by abundant raw materials, water sources, and faunal availability. Results demonstrate the interplay between freehand and bipolar knapping, reflecting a flexible technological strategy to exploit the available radiolarite. Freehand percussion was mainly used in flake production, while the bipolar technique facilitated initial core reduction and late-stage exhaustion. The consistent microlithisation at the site is also evident in the exploitation of other locally available raw materials, such as limestone, flint, and quartz, supporting previous studies demonstrating small flakes’ effectiveness in diverse tasks. Technological patterns at Marathousa 1 broadly correspond to those observed at other Middle Pleistocene small tool sites; however, its distinctive intersection of raw material availability, technological choices and functional demands provides new insights into regional patterns of lithic variability across Eurasia during this period.